Nineteen new species of Amphidraus Simon, 1900 (Salticidae: Euophryini) from Colombia, with comments about their conservation - Galvis, William (Zootaxa, 2017)
The Andean region of Northern South America is widely recognized as a hotspot with extreme levels of diversity, endemism, and threat. In a taxonomic study on jumping spiders from Colombia, nineteen new species of Amphidraus Simon, 1900 were found, all of which with small-scale endemic distributional patterns. Sixteen of these new species are described from the Andean region, eight of which being restricted to the Cundiboyacense high-Andean plateau (A. bochica sp. nov., A. guatavita sp. nov., A. mae sp. nov., A. pae sp. nov., A. sie sp. nov., A. sotairensis sp. nov., A. tisquesusa sp. nov. and A. tundama sp. nov.), in the Boyacá and Cundinamarca departments. The eight remaining Andean species are distributed out of this high-Andean plateau, in the Eastern Mountain Range of Boyacá (A. chie sp. nov., A. somondoco sp. nov. and A. sua sp. nov.), Cundinamarca (A. quinini sp. nov. and A. zaque sp. nov.), Huila (A. guaitipan sp. nov.) and Santander (A. zipa sp. nov.) departments, and in the Central Mountain Range of Risaralda department (A. quimbaya sp. nov.). Additionally, A. sikuani sp. nov. is described from the Eastern department of Meta, and A. colombianus sp. nov. and A. tanimuca sp. nov. from the Amazonian department of Vaupés. Finally, a map with these new records is included, along with a short comment about conservation of biota in the Andean region.